Worldwide trend in research on Candida albicans and cancer correlations: a comprehensive bibliometric analysis - Tang, Shiqin; Xu, Yanyan; Li, Xiaojing (Frontiers in Microbiology, 2024)
Objective Candida albicans (C. albicans), an opportunistic pathogen, is implicated in the carcinogenesis of various cancers, thereby significantly impacting human health. This study conducts an in-depth analysis of the prevailing research dynamics concerning the relationship between C. albicans and cancer over the past decade, offering a comprehensive overview of the knowledge structure and emerging focal points in this field through bibliometric scrutiny. Methods A methodical quantitative and visual scrutiny of pertinent literature from the Web of Science Core Collection (WoSCC) spanning the previous decade was carried out employing VOS Viewer and CiteSpace software. Results From January 1, 2014, to January 1, 2024, a comprehensive corpus of 1,259 articles was delineated. Prominent research institutions included the Egyptian Knowledge Bank, Cairo University, and King Saud University. The top three prolific countries were the United States, China, and India. Among the authors, Mohamed, Gehad G., Mahmoud, Walaa H., and Netea, Mihai G., emerged as the most prolific, with Pfaller, Ma being distinguished as the most frequently cited author. The journal Molecules published the highest number of articles, while PLoS One had the highest citation count. Nature had the highest impact factor. The research focal points in this field encompassed the interactions between C. albicans and cancer, the correlation with oral cancer, the underlying mechanisms of C. albicans carcinogenic potential, as well as antifungal and anticancer therapies. Conclusion This investigation constitutes a pioneering bibliometric analysis elucidating the trends and advancements in research regarding the correlation between C. albicans and cancer. Said analyses uncover the prevailing research focal points and trends, offering insightful guidance for subsequent inquiry in this domain. Systematic review registration https://www.webofscience.com/wos/woscc/summary/df33afba-f843-41e8-b932-cb3678eb8243-e92e7316/relevance/1